If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 10 = 10y Reorder the terms: 10 + -2x = 10y Solving 10 + -2x = 10y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -2x = -10 + 10y Combine like terms: 10 + -10 = 0 0 + -2x = -10 + 10y -2x = -10 + 10y Divide each side by '-2'. x = 5 + -5y Simplifying x = 5 + -5y
| 1.1x+2-4.1x=8 | | X+2/2=10-x+2/3 | | -3x+y=-17 | | 5x-32.4=x | | 0.4x+0.9=-1.1 | | 18-7x=2x | | 2/9r+10=-10 | | 6(2-t)-(4-4t)=5 | | 4(3-t)-(2-2t)=7 | | 9.8+x/5=10.4 | | 7x=5y | | y(3y+8)=-5 | | (r/-7)-5=-6 | | 3x+4=(x-8) | | 2y+8=10y | | w^2-14w-72=0 | | c=5(F-32)/9 | | 60x^2-44x-5= | | -24+6=-5 | | -10x-3x-3x=-70 | | (3x-6)(5x-9)= | | 3x/4-1 | | 2x^3=35 | | x+2x+x+27=167 | | -630=76x+126y | | 7.5+0.5x=3/4x | | 3r^2+r-24=0 | | 9x+2y=36 | | 4t^2-3t-5=0 | | -8x-7x=64 | | 5x-10+5x=-10 | | 5x-3=3x-11 |